PENGARUH PERAN KELOMPOK TANI TERHADAP KESEJAHTERAAN PETANI KOPI DI KELOMPOK TANI RAHAYU IV KABUPATEN SEMARANG - Muhammad Satrio Kurniawan; Siwi Gayatri; Tutik Dalmiyatun (JURNAL VIGOR, 2021)
This research was focused to determine the effect of the farmer groups toward coffee farmer’s welfare and it have been conducted on July-August 2020 in Rahayu IV’s Farmer Group, Semarang Regency. This research was aimed to (1) analyze farmer groups role, consists of learning media, a vehicle for cooperation, production units, and business units in Rahayu IV’s Farmer Group, (2) analyze the welfare of Rahayu IV's Farmer Group members, and (3) analyze the influences of farmer groups role toward the farmer’s welfare in Semarang Regency. The location of this research was determined purposively because it was an active farmer group, doing coffee farming from upstream to downstream, and get a lot of achievements. Survey method was used in this research. The number of respondents was 32 respondents who were all members of Rahayu IV's Farmer Group. Primary data and secondary data were used in this research. The data analysis application used the SPSS 23.0 program. Data analysis used multiple linear regression analysis. The result showed that the farmer groups role, consist of learning media, cooperation, production units, and business units had been in line with expectations of farmer group members, most members were already economically and socially prosperous, and partially and simultaneously, there was an influence of farmer groups role towards farmer’s welfare. The coefficient of determination was 83.9%.Keywords: black coffee; farmer groups; the role of farmer groups; welfare